Regulasi Hate speech di Media Sosial Dalam Kontestasi PEMILU 2024 di Indonesia(Kajian Lintas Sektoral) - yusri, yusri (Lembaga Sepercenter, 2024)
This article discusses regulations regarding hate speech on social media in the 2024 election contestation in Indonesia. Every national agenda always has regulations with the aim of ensuring that the agenda runs without any obstacles. The reality is that in every national agenda there are always bad things happening. This is what causes the author to examine regulations regarding hate speech on social media in the 2024 election contestation. The elections have been held, but here the existing regulations regarding hate speech are discussed through a descriptive qualitative study which is linked to the concept of human relations, systems theory and theory X and Y. It can be described that hate speech regulations starting from creation to law enforcement efforts towards these regulations will only be effective if everything related to them is adapted to the concept of human relations, in accordance with systems theory, and in accordance with theories X and Y. Actors must be forced to follow existing rules in order to become the sovereignty of the Indonesian State.